[Blok znaczków podziemnych "IV rocznica strajków rolników polskich"] . Sheet of unofficial stamps "Fourth anniversary of the strike of Polish Farmers" - Solidarność Rolników - Fundusz Oporu Rolników. (Solidarność Rolników - Fundusz Oporu Rolników, 1985)
Green print on white paper, without perforation. Sheet with "Solidarność Rolników" and "Fundusz Oporu Rolników" imprint, commemorates the fourth anniversary of the farmer strikes in Rzeszów and Ustrzyki Dolne in 1981. The sheet with caption "Forth Anniversary of the strikes of Polish Farmers 1981-1985", and incipit from the patriotic song "Rota", bears an image of the peasant fighter from the 1794 Kościuszko Insurrection. The stamps represent banners of the Kościuszko fighters and captions with place and date of the strikes.